Persistent pain after vertebroplasty: Not to miss facet joint pain - Shakya, Bigen Man; Gurung, Renu; Shresth, Anil; Acharya, Binita; Shrestha, Nandini (Grande Medical Journal, 2020)
A patient can present with persistent pain even after vertebral compression fracture augmentation procedures. We report a case of a patient of carcinoma breast with L1 vertebral metastasis and fracture for which vertebroplasty was performed abroad. The patient had severe pain even after the procedure and multiple therapies. The patient’s pain was finally relieved with radiofrequency ablation of target medial branch, which highlights the importance of facet joint as source of pain generator in such group of patients.